2020
DOI: 10.1177/0363546520908604
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Scapular Kinematics and Muscle Activity by Use of Fine-Wire Electrodes During Shoulder Exercises

Abstract: Background: During nonoperative or postoperative rehabilitation after sports injuries, exercise selection is often based on minimal load on the injured/repaired glenohumeral structures, while optimally activating scapulothoracic muscles. Previous research explored scapular muscle activity during rehabilitation exercises using surface electromyography (EMG). However, limited information exists about the deeper lying muscle activity, measured with fine-wire electrodes, even more in combination with 3-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…More recently, the activation patterns of the deep scapular stabilizers, such as the levator scapulae (LS), rhomboid major (RM), and pectoralis minor (Pm) muscles, were explored with fine-wire EMG during rehabilitation exercises. 2,7,8,10 Exploring the activation of these muscles gives a new dimension of information that may influence the clinicians' exercise choice. Moreover, knowledge about the optimal muscle activation ratio (the relative activity of one muscle in perspective to another, rather than absolute levels of activity) may be of importance for improving scapular muscle strength and balance.…”
mentioning
confidence: 99%
“…More recently, the activation patterns of the deep scapular stabilizers, such as the levator scapulae (LS), rhomboid major (RM), and pectoralis minor (Pm) muscles, were explored with fine-wire EMG during rehabilitation exercises. 2,7,8,10 Exploring the activation of these muscles gives a new dimension of information that may influence the clinicians' exercise choice. Moreover, knowledge about the optimal muscle activation ratio (the relative activity of one muscle in perspective to another, rather than absolute levels of activity) may be of importance for improving scapular muscle strength and balance.…”
mentioning
confidence: 99%
“…In our study, Rhom activity was not significantly different between the exercises. Moseley et al 33 and Berckmans et al 4 reported that the main function of the Rhom was scapular retraction. The scapular external rotation movement in scapular retraction increases with trunk rotation.…”
Section: Discussionmentioning
confidence: 99%
“… 47 Rhom muscle activity increases with increased scapular external rotation movement. 4 Exercises in the limb position parallel to the direction of the muscle fibers results in higher muscle activity. 32 , 37 In this study, the trunk rotation exercise, which required trunk rotation motion, and the A-exercise, in which the direction of movement was close to the direction of the oblique Rhom muscle fibers, were expected to show higher muscle activity, but no significant difference was found between the exercises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a standardized method to assess the sensorimotor function of the shoulder is yet to be determined. Other commonly used methods are the joint position sense and kinesthesia examinations [26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%